If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -7q = -15 + -15q Solving 7 + -7q = -15 + -15q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '15q' to each side of the equation. 7 + -7q + 15q = -15 + -15q + 15q Combine like terms: -7q + 15q = 8q 7 + 8q = -15 + -15q + 15q Combine like terms: -15q + 15q = 0 7 + 8q = -15 + 0 7 + 8q = -15 Add '-7' to each side of the equation. 7 + -7 + 8q = -15 + -7 Combine like terms: 7 + -7 = 0 0 + 8q = -15 + -7 8q = -15 + -7 Combine like terms: -15 + -7 = -22 8q = -22 Divide each side by '8'. q = -2.75 Simplifying q = -2.75
| 2=3u+8 | | -30x+-60+9=30 | | .25x+.1x+.05x=14 | | 64-12*2-6/3=x | | y-7=-2(x-2) | | 8.7n+4.5-3.2n=37.5 | | X-3.5=2.25 | | 5(-6d+12)= | | -35+4x=-2x+31 | | Y+6=3(x-2) | | 8.7n+4.5-3.2n=375 | | 3y+7=x-13 | | P=$1440/4 | | 3(2y+1)-5(12y-7)+(6y-1)=37 | | P=$1440/5 | | 13.2=t4.4 | | -4r-9=-14-3r | | x+4+3x=31 | | -2x-17=13-4x | | 4s^2=-36 | | -2Xx=5 | | 12-9x+45=-1+x | | R+25=9 | | 3x+1+4x=7x-3 | | 5d=9/10 | | 6x-17=13-4x | | 27.50x+23.25x=17 | | -9b=153 | | 28=4+11 | | (8x+1)(x-7)=(2x-3)(4x+5) | | 5(z+1)=4(z-8)+z | | 2q+58=-2+-4q |